Educational equity and opportunity to learn: Access to teachers in Brazil - Lara Elena Ramos Simielli (Arizona State University, 2017)
The goal of this article is to evaluate students' access to qualified teachers (regarding teacher education and experience), from 2001 to 2011 in Brazil. A logistic model was developed, with teacher characteristics as dependent variables and four independent variables: student characteristics (gender, race and socioeconomic status), system characteristics (private or public schools), states (26 states and one federal district) and territory (urban or rural). The database comes from the SAEB statistics, in Portuguese and Mathematics, on fifth and ninth grades. The results indicate the importance of the socioeconomic status in determining educational opportunities and the existence of three evolution patterns concerning the access to qualified teachers from 2001 to 2011. The final considerations focus on three actions: the definition of minimum standards, the development of compensatory policies as well as positive discrimination; and the investment on teacher training.